PROBLEMS OF IMPLEMENTATION OF ELECTRONIC DOCUMENT MANAGEMENT SYSTEM IN THE PRODUCTION DEPARTMENTS OF CONSTRUCTION ORGANIZATIONS - A. Saitgaraev (Вестник университета, 2016)
This article analyzes the legal and administrative aspects of the introduction of electronic document management system in the production departments of construction organizations, as well as the necessity of implementation of these systems. The article also highlights the areas of human activity, in which the electronic document management system has firmly taken its place.